Test-retest reliability of body center of mass sway during Five Time Sit to Stand Test; FTSST assessed by Kinect-Based Exergames device in healthy elderly - Tapanya, Weerasak; Kumfu, Sirintip; Sangkarit, Noppharath; Puntumetakul, Rungthip (Srinagarind Medical Journal, 2022)
Background and Objective: The main factor of fall risk prevention in elderly is fall risk assessment; FRA. Therefore, reliable assessment method is very important. The purpose of this study was to define the test-retest reliability of body center of mass (COM) sway assessment while perform sit to stand using Kinect-Based Exergames device in older adults. Methods: Twenty older adults aged more than 60 years (mean age was 67.30 ± 5.58 years) were instructed to performed Five Time Sit to Stand Test (FTSST) while the body COM sway in 3 directions were evaluated by Kinect and software which was developed. The participants were assessed two trials with 1-week resting period. The Intraclass correlation coefficients (ICC3,1) was used to explore test-retest reliability and significant levels were set at p < 0.05. Results: The results showed that test-retest reliability of body COM sway during FTSST was good reliability (ICC3,1 were between 0.83 – 0.90). Conclusion: The kinematics assessment of body COM sway during FTSST which were evaluated by Kinect and software which was developed is test-retest reliable assessment.